Evaluation of efficacy of commercial denture cleansing agents to reduce the fungal biofilm activity from heat polymerized denture acrylic resin: An in vitro study - Mithilesh M Dhamande; Ashok J Pakhan; Ram U Thombare; Shyam L Ghodpage (Wolters Kluwer Medknow Publications, 2012)
Aims: To compare and evaluate Candida removing effects of three most commonly available varieties of commercial denture cleansers from heat polymerized acrylic resins. To compare and evaluate Candida lytic effects of denture cleansers. To assess the effect of time on ability of denture cleansers in reducing Candidal biofilm. Materials and Methods: A specially designed metal mold was fabricated to obtain wax plates of uniform dimensions which were used to fabricate heat cure acrylic resin plates. A square-shaped window of dimension 15 mm and thickness of 1.5 mm was provided in metal mould to simulate thickness of denture base. All samples used in this study were prepared using this mould. Candida albicans colonies were then cultured on this acrylic resin plates by colonization assay. Yeast removing test for samples was performed using microscope and yeast lytic test was performed using photo colorimeter. Results: Denture cleanser D2 showed the highest Candida removing activity when compared with cleansers D1, D3, and control solution. Denture cleansers D2 showed increased yeast lytic ability when compared with denture cleansers D1, D3, and control solution. More time span shared a definite influence on yeast lytic ability of denture cleansers. Conclusions: The effect of cleansing agents on removal of colonized yeasts particularly fungal biofilm from acrylic resins was assessed for clinical implications. The observation indicated superior performance of cleanser D2 when compared with D1 and D3 even though they all belong to same chemical group of alkaline peroxide. The increased effectiveness may be due to presence of sodium lauryl sulphate in formula of D2.